Mapping the state of the art of scientific production on requirements engineering research: a bibliometric analysis - Hassan, Sa'adah; Ahmi, Aidi (IGI Global Publishing, 2022)
Requirements engineering (RE) is gaining acceptance by industries and practitioners as a significant process in systems development. Similarly, the publications on the research related to the RE topic progresses. However, there is a lack of study on the progressions of this research based on a bibliographic portfolio. This paper presents the emergence of the RE field and mapping the state of the art of scientific production using a bibliometric survey approach. This study identifies the research trends based on the observations of scientific production over the past two decades. Quantitative and qualitative information in requirements engineering research through various bibliographic attributes are presented, such as the leading journals, top-cited articles, top authors, and top countries. Research trends in RE can be observed based on the number of research themes, and the involvement of various disciplines from RE begin to get acknowledged until this study was conducted. The results provide evidence and an overview of future directions in this research field.